Fuga e ritorno: Italian-Canadian Narratives - Pivato, Joseph (Italian Canadiana)

(untitled) (Iter Press, 2021)
Many Italian-Canadian authors have been stimulated to explore their dual identity after a return trip to Italy. They confront the myth of nostalgia as an emotional blind-spot to the harsh realities of past miseria and present-day conflicts in Italian society. Women writers such as Mary di Michele, Caterina Edwards, Licia Canton and Rina Cralli are particularly critical of the position of women in Italy and the whole nostalgia sentimentality promoted by Italian popular culture and music. Pasquale Verdicchio’s whole writing career has been a systematic rejection of the thematics of nostalgia.